Parameter optimization of copper nanoparticle synthesis by electrodeposition process using RSM and CS. (2021) - Tamilvanan, A.; Balamurugan, K.; Mohanraj, T.; Selvakumar, P.; Madhankumar, B.
Abstract: Now-a-days, more concentration attention has been given for synthesizing of copper (Cu) nanoparticles due to its excellent physical and chemical properties. Different approaches are available to synthesize the Cu nanoparticles. Electrodeposition is an easier and simple approach to synthesize the Cu nanoparticles with high purity. The properties of Cu nanoparticles depend on their synthesis approach and electrolysis process parameters. In this work, response surface methodology (RSM), cuckoo search (CS) algorithm was used to optimize the electrodeposition process parameters like concentration of CuSO4 (4–6 g l −1 ), electrode potential difference (12–27 V) and electrode distance (3–5 cm) on mean size of Cu nanoparticles. The mean particle size of 21.55 nm was obtained with the electrodeposition parameters of (4 g l −1 ) CuSO4, (3 cm) electrode distance and (27 V) electrode potential difference. The particle size obtained from the experimental result was 20 nm which was very closer to the predicted result (21.5 nm). The size and morphology of Cu nanoparticle were analyzed by using scanning electron microscope and X-ray diffraction technique.